Correlation Between Students’ Perception on English Language Learning and Their English Speaking Performance - Wedari, Ni Putu Dhita Vasya; Skolastika, I Made Perdana (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
The present study is entitled Correlation Between Students’ Perception of English Language Learning and Their English-speaking Performance. The study aimed to investigate whether there is a significant correlation between students’ perception and the speaking performance of the third-semester students in the Faculty of Foreign Languages Mahasaraswati Denpasar. The data were obtained by the quantitative method in correlational design. The study was conducted at the Faculty of Foreign Languages Mahasaraswati Denpasar. The population was 189 Faculty of Foreign Languages students in Mahasaraswati Denpasar, divided into 6 classes.This study applied the purposive sampling method, which took 16 students of the same class. The instruments used in collecting the data of two variables were the perception of the English Language online learning questionnaire and oral test video of speaking performance. The questionnaire used Sugiyono’s perception scale, which contained 32 valid questions, and an oral test video rubric to measure speaking performance based on Harmer. In analyzing the data, SPSS software version 26 and Cronbach's Alpha formula were used to determine the reliability of the questionnaire. The study findings were that the third-semester students in the Faculty of Foreign Languages Mahasaraswati Denpasar had 50% high perception with a mean score of 116.81, and their speaking performance was at a minimal level of 43,75% with a mean score of 82,5. The coefficient relationship (rxy): 0.583. Based on the result of the study, it could be concluded that the perception of English Language online learning had a highlypositive relationship with the speaking ability of the chosen third-semester students in the Faculty of Foreign Languages Mahasaraswati Denpasar.